2004
DOI: 10.1590/s1415-47572004000300008
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA content in 20 species of Siluriformes (Teleostei: Ostariophysi) from the Neotropical region

Abstract: In the present study, 20 species of Siluriformes fish were analyzed in order to determine their nuclear DNA content and compare these data with their diploid number. In addition, the extension and importance of the changes that occurred during the process of diversification in the group of Neotropical freshwater catfish were investigated. The only species studied of the family Doradidae, Rhinodoras d'orbignyi (2n = 58), presented 3.46 ± 0.13 pg of DNA. Among the species of the family Heptapteridae, the values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Analysis of the nuclear DNA content of species in the Loricariidae family conducted by Fenerich et al (2004) showed that the variation in diploid number does not seem to be directly related to the genome size. Thus, Hypostomus sp.…”
Section: Polyploidy and Evolutionmentioning
confidence: 99%
“…Analysis of the nuclear DNA content of species in the Loricariidae family conducted by Fenerich et al (2004) showed that the variation in diploid number does not seem to be directly related to the genome size. Thus, Hypostomus sp.…”
Section: Polyploidy and Evolutionmentioning
confidence: 99%
“…(average = 2.62 ± 0.19 pg/nucleus) and T. cf. iheringi (average = 2.3 ± 0.23 pg/nucleus) (Fenerich et al, 2004). These findings show that this cellular parameter varies widely in Trichomycterus.…”
Section: Sato Et Al (2004) Grouped the Cis-andeanmentioning
confidence: 54%
“…Of note are the considerable variations in nuclear DNA contents of three species of the same genus, even though they possess the same diploid number (2n = 54). However, this is not atypical in fishes, given that this type of interspecific variation is often observed at the genus level (Carvalho et al, 1998;Fenerich et al, 2004), and can result from different processes, such as duplication and/or loss of chromosome segments, or differential accumulation of repeated DNA elements in the genome, as already well documented in higher vertebrates (Hartl, 2000). The nuclear DNA content Colihueque et al 281 values described for Trichomycterys so far (2.3-5.04 pg/nucleus) are higher than the average described for fishes (2 pg/nucleus; Hinegardner and Rosen, 1972), although they fall within the upper range described for various species of Siluriformes (1.04-8.75 pg/nucleus; Carvalho et al, 1998).…”
Section: Sato Et Al (2004) Grouped the Cis-andeanmentioning
confidence: 99%
“…This fast chromosome evolution in Hypostomus may be followed by some event of polyploidy as suggested by Fenerich et al (2004). Interestingly, other loricariid group with extensive chromosome diversification is the genus Corydoras that also experience some events of polyploidy (Shimabukuro-Dias et al 2004).…”
Section: Discussionmentioning
confidence: 97%